Preliminary Study of Bird Species Composition in Kawang Forest Reserve (KFR), Papar, Sabah - Nurliza Hasmat; Lim, Wing Shen; Andy Russel Mojiol (e-VIBS, Faculty of Science and Natural Resources, 2020)
Birds have their own importance in the ecosystem for maintaining the sustainable population levels of their prey and predator, and for plant reproduction as pollinators. The preliminary study about bird species composition was conducted in Kawang Forest Reserve (KFR), Papar in August 2019. The main objective of this study is to determine the bird species according to its conservation status and comparing bird composition with respect to its family using the mist-net method. This survey was conducted for 5 days started from 27th August to 31st August 2020 at two different areas where 4 mist-net were installed near the river and the other 4 mist-net were installed on the ridges. The results showed that 39 individuals with 19 different species belong to 9 different families had been found in the areas. The Emerald Dove (Chalpcaphaps indica) species were high number of individual founded while Bulbul species from Pycnonotidae family were high species founded in KFR.